Comparison of I-V Curves Between the Experiment of Corona Discharge on Gradient Line-To-Plane (GL-P) Configuration and The Mathematical Approach - Susilo Hadi; Asep Yoyo Wardaya; Zaenul Muhlisin; Jatmiko Endro Suseno; Pandji Triadyaksa; Ali Khumaeni; Muhammad Nur (Journal of Physics and Its Applications, 2021)
Research has been conducted on the comparison of the I-V characteristic curve between mathematical study and experiment of the generation of negative DC corona discharge in the Gradient Line-to-Plane (GL-P) electrode configuration. The reason for this research is to calculate the suitability of the corona discharge electrical current between the mathematical and experimental study. The active electrode used has length 2 cm and height 4 cm. This research is conducted with variations in the sharpness angle of the active electrode (θ) 300, 450, and 600 and variations in the distance between the electrodes () 2 cm, 3 cm, and 4 cm. The mathematical formulation of the value of the corona discharge electrical current in the configuration of the GL-P electrode is obtained by using the geometric concept approach, which is the formulation of the capacitance value of the ordinary electrical circuit, with the addition of the multiplication factor value k in the sharp area of the active electrode, because in that area the greatest plasma flow distance is obtained. The value of the multiplication factor  is obtained by fitting the curve between mathematical study and experiments. The I-V curve between the mathematical study and the corona discharge generation experiment has a high degree of similarity with the smallest percentage contacting point of 37.50%.The value of the multiplication factor  is influenced by the sharpness angle of the active electrode shape and the distance between the electrodes.